Predictors of Averse Events After Total Laryngectomy: An Analysis of the 2005-2011 NSQIP Datasets - Mlodinow, Alexei; Khavanin, Nima; Shires, Courtney; Samant, Sandeep; Ver Halen, Jon; Kim, John (Journal of Otolaryngology Advances, 2014)
Background: We reviewed the 2005-2011 ACS-NSQIP database to evaluate factors associated with adverse events (AE) after total laryngectomy (TL). Methods: All total laryngectomies performed from 2006 to 2011 were identified for analysis. The cohort was characterized with respect to preoperative and demographic characteristics, complications, reoperation, and mortality. Results: 493 cases were identified. Complications of any category occurred in 189 cases (38.3%). Factors that were found to confer significant risk for medical complications were increased age (dds Ratio (OR) 1.03), prior PCI (OR 2.84), disseminated cancer (OR 2.47), chronic steroid/immunosuppresion use (OR 2.87), unintended weight loss > 10% over 6 months prior to surgery (OR 2.02), increasing work RVU total (OR 1.02), and increased anesthesia Z-score (OR 1.31). Only increased anesthesia Z-score (OR 1.27) was found to be a statistically significant risk factor for surgical complications. Chronic steroid/immunosuppression use (OR 3.16) and increased anesthesia Z-score (OR 1.29) were both found to be statistically significant risk factors of reoperation within 30 days. Conclusions: NSQIP is the only dataset that correctly discerns between minimally invasive and wide excision in laryngectomy. The use of the NSQIP dataset may be imperfect, as pertinent details of chemotherapy and radiation, and procedure-specific complications, including fistula formation, are not tracked. In spite of this, our findings suggest avenues for improvement in the care of TL patients, and suggest directions for a laryngectomy-specific outcomes database.
Keywords: laryngectomy; NSQIP; outcomes; mortality; complications